Genetic Variation in Telomere Maintenance Genes, Telomere Length and Breast Cancer Risk - Shen, Jing (Public Library of Science, 2012)
BACKGROUND: Telomeres at the ends of eukaryotic chromosomes play a critical role in maintaining the integrity and stability of the genome and participate in the initiation of DNA damage/repair responses. METHODS: We performed a case-control study to evaluate the role of three SNPs (TERT-07, TERT-54 and POT1-03) in telomere maintenance genes previously found to be significantly associated with breast cancer risk. We used sister-sets obtained from the New York site of the Breast Cancer Family Registry (BCFR). Among the 313 sister-sets, there were 333 breast cancer cases and 409 unaffected sisters who were evaluated in the current study. We separately applied conditional logistic regression and generalized estimating equations (GEE) models to evaluate associations between the three SNPs and breast cancer risk within sister-sets. We examined the associations between genotype, covariates and telomere length among unaffected sisters using a GEE model. RESULTS: We found no significant associations between the three SNPs in telomere maintenance genes and breast cancer risk by both conditional logistic regression and GEE models, nor were these SNPs significantly related to telomere length. Among unaffected sisters, shortened telomeres were statistically significantly correlated with never hormone replacement therapy (HRT) use. Increased duration of HRT use was significantly associated with reduced telomere length. The means of telomere length were 0.77 (SD = 0.35) for never HRT use, 0.67 (SD = 0.29) for HRT use <5yrs and 0.59 (SD = 0.24) for HRT use ≥5yrs after adjusting for age of blood donation and race and ethnicity. CONCLUSIONS: We found that exogenous hormonal exposure was inversely associated with telomere length. No significant associations between genetic variants and telomere length or breast cancer risk were observed. These findings provide initial evidence to understand hormonal exposure in the regulation of telomere length and breast cancer risk but need replication in prospective studies.